A STUDY OF STUDENTS’ ABILITY IN UNDERSTANDING TOEFL’S READING SECTION AT TOEFL PREPARATION CLASS OF “ UNIVERSITAS SUMATERA BARAT” - Warni, Asis; Christy Jufry, Allen (Ensiklopedia Education Review, 2023)
The research is aimed to figure out the students’ ability in understanding TOEFL’s reading section at TOEFL Preparation class of “Universitas Sumatera Barat”. The descriptive method and  total sampling technique are employed in this research as methodology of the research and the way in set up the sample. There are 33 students of the TOEFL preparation class and all of them are taken as the sample.Reading test is used as the instrument of the study. The result of data from the students’ ability in understanding TOEFL’s reading section are as the following: The easiest question for the learners is stated detail question about 28 students or 85% can answer the questions. The next, guessing easy word from context, 27 learners or 82% had the right answers. In addition, pronoun, tone,purpose and course are also easy questions for the students, 26 students or 79% overcome the questoion correctly. The most difficult problems or questions for the learner are about definition from context clues, 22 students or 67% can answer that questions, the implied detail question, only 21 students or 64% answered it correctly. Next, organization of idea, 20 learners or 61% got the right answers.Keywords: Ability, Reading, TOEFL.